The effectiveness of honey supplementation in feed for improving goldfish fingerling Carassius auratus immune system against Aeromonas hydrophila bacteria attack - Rosidah, Rosidah; Subhan, Ujang; Mulyani, Yuniar; Dermawan, Rifai (Jurnal Akuakultur Indonesia, 2019)
ABSTRACT The attack of Aeromonas hydrophila bacteria can cause mortality in goldfish approximately 100%. The controlling of this bacterial attack can be done through increased fish immunity. Honey is one of the natural ingredients that increases body immune system. This study aimed to determine the effective dose of honey supplemented in feed to increase goldfish fingerling resistance for disease prevention. Fish used in this study were goldfish fingerlings with 3.5 g average weight. This study was done using experimental complete randomized design method with five treatments and three replications. Treatments given were honey supplementation in feed with 0 ml/kg (A) as control treatment, 150 ml/kg (B), 200 ml/kg (C), 250 ml/kg (D), and 300 ml/kg (E). The result showed that honey supplementation in feed was effective to improve goldfish fingerlings resistance against Aeromonas hydrophila bacterial attack. The supplementation of honey in feed with 200 ml/kg was the best treatment for inducing goldfish fingerlings against A. hydrophila. This was proven by the increased white blood cells (leucocytes) (27.84 ± 5.07%) followed with no apparent clinical symptoms after attacked by A.hydrophila, such as hemorrhage, necrosis, exophthalmia or dropsy, besides showing the highest survival rate with 73.33 ± 11.5%. Keywords : Aeromonas hydophila, goldfish, honey, leucocyte, resistance ABSTRAK Serangan bakteri Aeromonas hydrophila dapat menyebabkan kematian ikan mas koki hingga mencapai 100%. Penanggulangan serangan bakteri tersebut dapat dilakukan dengan meningkatkan ketahanan tubuh (imun) ikan.  Madu merupakan salah satu bahan alami yang dapat meningkatkan ketahanan tubuh. Penelitian ini bertujuan untuk menentukan dosis efektif penambahan madu pada pakan untuk meningkatkan daya tahan tubuh benih ikan mas koki dalam upaya pencegahan penyakit aeromonasis. Benih yang digunakan adalah benih ikan mas koki berukuran 3.5 gram. Metode penelitian yang digunakan adalah rancangan acak lengkap (RAL) dengan lima perlakuan dan tiga ulangan. Perlakuan yang digunakan adalah penambahan madu pada pakan dengan dosis 0 mL/kg (A) sebagai kontrol, 150 mL/kg (B), 200 mL/kg (C), 250 mL/kg (D), 300 mL/kg (E). Hasil penelitian menunjukkan bahwa penambahan madu ke dalam pakan efektif dalam meningkatkan ketahanan tubuh ikan mas koki terhadap serangan Aeromonas hydrophila. Dosis 200 ml/kg pakan memberikan hasil terbaik dalam meningkatkan ketahanan tubuh ikan mas koki terhadap serangan A. hydrophila terlihat dari peningkatan jumlah sel darah putih terbesar (27.84 ± 5.07%), tidak nampak adanya gejala klinis ikan terserang A. hydrophila seperti hemoragi, necrosis, exophthalmia maupun dropsy dan menghasilkan kelangsungan hidup benih ikan mas koki tertinggi yaitu sebesar 73.33 ± 11.5%. Kata kunci: Aeromonas hydrophila, ketahanan tubuh, ikan mas koki, madu, sel darah putih.